Waterpipe tobacco smoking impact on public health: implications for policy - Martinasek MP; Gibson-Young LM; Davis JN; McDermott RJ (Dove Medical Press, 2015)
Mary P Martinasek,1 Linda M Gibson-Young,2 Janiece N Davis,3 Robert J McDermott41Public Health Department of Health Sciences and Human Performance, University of Tampa, Kennedy Boulevard, Tampa, FL, 2College of Nursing and Health Sciences, Texas A&M University: Corpus Christi, Corpus Christi, TX, 3Department of Health – Palm Beach County, West Palm beach, FL, 4Department of Population Health Sciences, School of Medicine and Public Health, University of Wisconsin-Madison, Madison, WI, USABackground: Given the increasing evidence of its negative health effects, including contributions to both infectious and chronic diseases, waterpipe tobacco smoking raises public health concerns beyond even those presented by traditional smoking. Methods: Identification of Clean Indoor Air Acts (CIAAs) from each of the 50 United States and District of Columbia were retrieved and examined for inclusion of regulatory measures where waterpipe tobacco smoking is concerned. Several instances of exemption to current CIAAs policies were identified. The cumulative policy lens is presented in this study. Results: States vary in their inclusion of explicit wording regarding CIAAs to the point where waterpipe tobacco smoking, unlike traditional smoking products, is excluded from some legislation, thereby limiting authorities’ ability to carry out enforcement. Conclusion: Consistent, comprehensive, and unambiguous legislative language is necessary to prevent establishments where waterpipe tobacco smoking occurs from skirting legislation and other forms of regulatory control. Stricter laws are needed due to the increasing negative health impact on both the smoker and the bystander. Actions at both the federal and state levels may be needed to control health risks, particularly among youth and young adult populations.Keywords: health policy, waterpipe tobacco, hookah smoking, tobacco regulation